KEPRIBADIAN TOKOH UTAMA DALAM NOVEL 24 WAJAH BILLY KARYA DANIEL KEYES - Auliya Anggraini; Antonius Totok Priyadi; Sesilia Seli (Universitas Tanjungpura, 2019)
AbstractThis study is to identify the main character’s personality in the novel 24 Wajah Billy by Daniel Keyes, and to describe its relationship to id, ego, and super-ego as the aspects and factors emerging human’s personality; that is to describe the implementation of the results into the Indonesian instructions at school. The benefit of this study are devided into two categories: practical and theoritical. The theory applied in the study was psychoanalysis by Sigmund Freud. This study using the descriptive method and psychoanalysis approach. The data sources in this study is novel 24 wajah billy, while the data are words, sentences, and events. The data collection techniques in this study used documentary study technique. Data collections tool in this study is self-research as a key instrument. The analysis shows that (1) the main character in the novel has fifteen personalities that are seen from the aspect of id, ego, and superego. (2) The factors emerging the personalities are viewed based on seven personal aspects. (3) The result was implemented into the Indonesian language and arts subject material on the basic competencies 3.9 and 4.9 of third grade on the senior high school. Keywords: Personality, The main character, Novel.